Small‐scale distributions in an indoor environment at 94 GHz. Issue 7 (15th July 2017) - Reig, J.; Martinez‐Ingles, M. T.; Molina‐Garcia‐Pardo, J. M.; Rubio, L.; Rodrigo‐Peñarrocha, V. M.
Abstract: In this paper, an extensive multiple‐input multiple‐output measurement campaign in a lab environment has been conducted at the 94 GHz band. Using a vector network analyzer, updown converters, and omnidirectional antennas displaced in virtual arrays, we have obtained an estimation of the distribution parameters for the most usual distributions employed in the small‐scale fading modeling, i.e., Rayleigh, Rice, Nakagami‐ m and α ‐ μ, by using statistical inference techniques. Moreover, in this scenario the best fit distribution to the experimental data is the Weibull distribution, using the Kolmogorov‐Smirnov test. However, the α ‐ μ distribution provides the best fitting to the experimental results in terms of the lower tails of the distributions. Key Points: Estimation of the small‐scale distribution parameters at the 94 GHz band in line‐of‐sight condition in the frequency domain Weibull is the best fit distribution using the Kolmogorov‐Smirnov test The distribution alpha‐mu provides the best fitting to the measurements for the lower tails of the distribution